1984
DOI: 10.1002/ijc.2910330321
|View full text |Cite
|
Sign up to set email alerts
|

The serologically unique cell surface antigen of zajdela ascitic hepatoma is also its tumor‐associated transplantation antigen

Abstract: A unique cell surface antigen of a chemically induced rat hepatoma (Zajdela Ascitic Hepatoma, ZAH) has been identified serologically and purified to apparent homogeneity. ZAH cells, when injected subcutaneously or intradermally into syngeneic hosts, elicit a weak humoral antibody response directed against a single cell surface antigen. In spite of prolonged and extensive immunization, the syngeneic anti-tumor antibodies are solely of the IgM class. Antisera from such immunized animals lyse tumor cells in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 25 publications
3
41
0
1
Order By: Relevance
“…Heat shock protein 90 in combination with tumour-specific antigens has been demonstrated to produce specific antitumour immunity (Srivastava and Das, 1984;Palladino et al, 1987;Blachere et al, 1993;Udono et al, 1994;Janetzki et al, 2000). The clinical trial being reported in this paper was initiated in 1999 to help address the issue of whether treating MRCC patients with the autologous HSP90 product vitespen induces an antitumour response, and whether subcutaneous outpatient IL-2 can convert vitespen nonresponders into responders.…”
Section: Vaccination Of Metastatic Rcc Patients E Jonasch Et Almentioning
confidence: 99%
“…Heat shock protein 90 in combination with tumour-specific antigens has been demonstrated to produce specific antitumour immunity (Srivastava and Das, 1984;Palladino et al, 1987;Blachere et al, 1993;Udono et al, 1994;Janetzki et al, 2000). The clinical trial being reported in this paper was initiated in 1999 to help address the issue of whether treating MRCC patients with the autologous HSP90 product vitespen induces an antitumour response, and whether subcutaneous outpatient IL-2 can convert vitespen nonresponders into responders.…”
Section: Vaccination Of Metastatic Rcc Patients E Jonasch Et Almentioning
confidence: 99%
“…H eat shock proteins (HSPs) purified from antigen-expressing cells chaperone antigenic peptides generated in that cell (1)(2)(3)(4). Immunization with such HSP-peptide complexes purified from tumors or pathogen-infected cells elicits specific immunity directed against the tumor or pathogen, respectively (5)(6)(7).…”
mentioning
confidence: 99%
“…Fractions of tumor lysates were tested in vivo and revealed the HSPs as sought-after tumor-rejection antigens. 2,37,38 They included Gp96, 2,[38][39][40] Hsp90, 39,41 Hsc70/Hsp70 39,42,43 as well as calreticulin, 44,45 Hsp110 and Grp170. [46][47][48] In the ensuing years, these chaperones were extensively studied and successfully applied in preclinical cancer vaccination approaches (Table 1).…”
Section: Discovery Of Hsps Gp96 and Their Immunological Propertiesmentioning
confidence: 99%
“…2,38 A number of animal studies documented that Gp96 purified from tumors is able to initiate efficient tumorspecific CTL responses and protective immunity. Moreover, Gp96 works in both prophylactic and therapeutic protocols.…”
Section: Discovery Of Hsps Gp96 and Their Immunological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation